Design and Development of a Combined Calcium—Iron—Folic Acid Prenatal Supplement to Support Implementation of the New World Health Organization Recommendations for Calcium Supplementation during Pregnancy. (June 2014) - Phillips, Ashley Aimone M.; Zlotkin, Stanley H.; Baxter, Jo-Anna B.; Martinuzzi, Frank; Kadria, Tanush; Roth, Daniel E.
Background: Hypertensive diseases of pregnancy are important causes of maternal and perinatal mortality. Based on meta-analyses of efficacy trials of prenatal cal- cium supplementation to reduce the risk of hypertensive diseases of pregnancy, the World Health Organization recommends 1.5 to 2.0 g of elemental calcium per day for pregnant women with low dietary calcium intakes (as well as 60 mg of iron and 400 μg of folic acid). However, implementation of this recommendation is challenged by the size and number of calcium tablets required and the need to avoid concurrent ingestion of calcium and iron due to intraintestinal interactions. Objective: We developed a novel micronutrient powder containing microencapsulated pH-sensitive calcium in addition to iron and folic acid, designed to facilitate early intestinal iron release and delayed calcium release. Methods: Two pharmaceutical companies were con- tracted to develop a prototype, one of which was chosen for clinical testing. Calcium carbonate granules were coated with a trilayer pH-sensitive enteric coating using a fluid-bed spray coater. Iron and folic acid granules were encapsulated with a time-release coating. Iron and cal- cium dissolution profiles were assessed during exposure to acidic (pH 1.2) and/or basic (pH 5.8) media using a modified USP apparatus 1 (basket) method. Results: At pH 1.2, calcium and iron release was ≤ 10% and > 90% after 120 minutes, respectively. At pH 5.8, > 80% of total calcium was released after 90 minutes. Conclusions: Based on in vitro criteria, the sup- plement may be a promising approach for delivering calcium, iron, and folic acid as a single daily dose to preg- nant women in settings of low dietary intake of calcium.